The Association Between Self-reported Food Addiction Symptoms and Obesity Among Adults: A Cross-sectional Study - Alhaj, Omar A.; Mahmoud, Iman; Sharif, Amina; Saif, Zahra; Jahrami, Haitham; Morris, Keith (Current Nutrition & Food Science, 2022)
Background: The prevalence of overweight and obesity is still on the rise worldwide. Uncontrolled craving for specific foods has been associated with overweight/ obesity, categorizing them as possible abuse-related disorders with food addiction (FA) as their possible main phenotype. The association between FA and the onset of overweight/ obesity is still controversial, yet scientifically plausible and is the focus of many recent overweight/ obesityrelated investigations. Objective: The current study was the first to examine the association of FA symptoms and obesity among young Bahraini adults. Methods: This study was designed using a cross-sectional research method recruiting a convenience sample of 654 adults aged 18-35 years. FA prevalence using Yale Food Addiction Scale (YFAS), sociodemographic, and anthropometric data, were collected using an online self-declared, semi-structured questionnaire. The descriptive results of the YFAS survey and the sociodemographic and anthropometric information were reported using descriptive statistics. Multiple regression test was utilized to analyze the correlations among examined factors. Results: A total of 124 (18.96%) participants met the criteria for FA. Responses showed that females had a slightly higher proportion of FA compared to the male participants. Results also showed no statistically significant association between various body mass index (BMI) categories and YFAS. For overweight participants, gender p = 0.018 appeared to be a significant predictor for BMI; and for obese participants, age p=0.001 and sex p= 0.001 appeared to be significant predictors of BMI. Conclusion: No significant correlation was found between FA and BMI, age, and gender; on the other hand, age and gender were significant predictors for BMI.
Keywords: food items